Experimental study on combustion characteristics of blended fuel pool fires. (May 2019) - Wang, Xuehui; Zhou, Tiannian; Chen, Qinpei; He, Junjiang; Zhang, Zheng; Wang, Jian
Liquid–vapor phase equilibrium theories are used to analyze boiling processes of blended fuel pool fires, and the results show that there are two boiling mechanisms (azeotropism and non-azeotropism) for blended fuels compared with single-component fuels. A series of pool fire experiments were conducted to investigate the combustion characteristics of blended fuel pool fires. The experimental results showed that the two boiling mechanisms have different effects on the burning process of the fuel blends. The boiling temperature and composition varied for the non-azeotropic blends during the burning process and remained steady for azeotropic blends. Furthermore, the boiling temperature of azeotropic blends is lower than that of its components and ranges from a specific temperature to the boiling point of the less volatile component. The flame radiant fraction of the azeotropic blend was also relatively constant during the burning process, whereas that of the non-azeotropic blend varied in different stages of the burning process. Heskestad's flame height model and flame axial temperature distribution model are applicable for pool fires of azeotropic and non-azeotropic blends.